The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.dcn.2020.100859
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in accumbofrontal tract integrity relate to risky decisions under stress in adolescents and adults

Abstract: Psychosocial stress increases risky decision-making (DM). It is widely accepted that individual variation in neural phenotypes underlie variability in this behavioral tendency in adults, but is less examined in adolescents. Our goal was to test the hypothesis that the relation between neural phenotypes and stress-related risky DM is better characterized by individual variation than by age. Using diffusion tensor imaging (DTI) tractography to characterize the accumbofrontal tract, we determined if it uniquely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It is also notable that not all teens engage in problematic risk taking. Such behavioral differences likely stem from individual differences in the underlying drivers of risk taking including psychological and neurobiological factors (e.g., Uy & Galvan, 2020), in addition to differences in opportunity. As Khurana et al.…”
Section: Adolescent Decision Makingmentioning
confidence: 99%
“…It is also notable that not all teens engage in problematic risk taking. Such behavioral differences likely stem from individual differences in the underlying drivers of risk taking including psychological and neurobiological factors (e.g., Uy & Galvan, 2020), in addition to differences in opportunity. As Khurana et al.…”
Section: Adolescent Decision Makingmentioning
confidence: 99%
“…They found that neural connectivity exhibited less mature brain states under high‐emotions states, which was associated with greater risk preference in adolescents and young adults (Rudolph et al., 2017). In a study examining risk‐taking under self‐reported high‐stress conditions (as indexed with daily diary), multilevel logistic regression analyses revealed that although all participants were more likely to take risks as expected reward value increased, this behavior was greater under high versus low stress for individuals with low accumbofrontal tract integrity (i.e., less connectivity between the ventral striatum and frontal cortex; Uy & Galván, 2010). Results suggest that individual differences in brain structure and function are just as germane to characterizing risky decisions in adolescents as ontogeny.…”
Section: Part III Dynamic and Integrative Behaviors In Adolescencementioning
confidence: 99%
“…Amygdala reactivity to or functional connectivity with other brain regions while viewing negative stimuli, assessed either prior to a traumatic event or shortly therafter, prospectively predicts the onset of PTSD symptoms (e.g., Belleau et al, 2020;Fani et al, 2019;Lin et al, 2017; Stevens et al, 2017). van Rooij et al (2018) also demonstrated that blunted hippocampal responses to a response inhibition task within 24 hr of a traumatic event predicted worsened PTSD symptoms one month later. Some EEG research has similarly found that neural responses to reappraisals of negative emotions predict symptom reductions 1 year later in those with PTSD (Fitzgerald et al, 2018).…”
Section: Evidence For Common-cause Continuum and Predisposition Modelsmentioning
confidence: 95%
“…For men with low amygdala reactivity, however, socioeconomic resources at age 20 did not predict later antisocial behavior. In a recent experimental DTI study (Uy & Galván, 2020), in which participants had to make decisions that varied in terms of risk and reward, high accumbofrontal tract integrity moderated effects of daily levels of stress on decision making, such that elevated stress was linked to increased risk taking, but only if accumbofrontal integrity was low.…”
Section: Evidence For Person-by-environment Modelsmentioning
confidence: 99%